Imaging in ovarian cancer - Hebbar, Shripad S.; Moideen, Nilufer (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Ovarian cancer is the fifth most common cause of death from cancer in women after lung, breast, colon, and pancreatic cancer. The incidence of ovarian cancer rises continuously between the ages 30 and 70 years and peaks at 59 years of age. Ovarian cancer is more lethal than endometrial and cervical cancer combined due to delayed diagnosis. Owing to the lack of symptoms and early peritoneal dissemination, the tumour has spread outside the pelvis in approximately 70% of cases at the time of diagnosis. The stage at diagnosis is the most important prognostic factor. The 5-year survival rates drop from 93% in patients with localized disease to 28% in those with distant metastases. Bimanual pelvic exam and CA 125 levels have failed to allow consistent detection of ovarian malignancy.CA 125 is a high molecular weight glycoprotein recognised by the OC 125 monoclonal antibody (sensitivity & specificity is better with combination of TVS). Since the sensitivities of these techniques are below 50%, particularly ultrasonography, CT and MRI has become indispensable in detection and staging of ovarian malignancy.